Potential health benefits of aloe vera - Natalia Mikołajczak (Journal of Education, Health and Sport, 2018)
Introduction and aim: Aloe vera was known in antiquity, and then its versatile healing and cosmetic properties were used. It is a rich source of many chemical compounds; it has been shown that there are 75 biologically active compounds, i.e. vitamins, minerals, enzymes, sugars, phenolic compounds, sterols, amino acids. The aim of this article was to review the literature and gather information on the health benefits of aloe vera and its products.